Redesain dan Optimalisasi Ruang Parkir Fakultas Pertanian Kampus Bukit Jimbaran - RIJAL, MUHAMMAD; KOHDRATA, NANIEK; SEMARAJAYA, COKORDA GEDE ALIT (Jurnal Arsitektur Lansekap, 2016)
ABSTRACT Redesign and Optimalization of Parking Area, Faculty of Agriculture, Udayana University Bukit Jimbaran Campus Parking area is a facility that should be available to serve a site which has semi-public to public activities, such as a university campus. Faculty of Agriculture in Bukit Jimbaran Campus is also facing a problem to prepare a reasonably parking area for students and staffs at the vicinity. Especially within the past few years, there is a significant increase in numbers of students who use private transportation to campus. The more users and the longer class period and academic activities in campus will affect the capacity of parking spaces required in a given time. A good parking design and capacity is required to create a good atmosphere in parking habits. Some parking violations show that it has been caused by bad design. Therefore, a parking design model is proposed as a solution to the parking site in Faculty of Agriculture Udayana University, Bukit Jimbaran campus.